2022
DOI: 10.1136/heartjnl-2021-320417
|View full text |Cite
|
Sign up to set email alerts
|

Smartphone detection of atrial fibrillation using photoplethysmography: a systematic review and meta-analysis

Abstract: ObjectivesTimely diagnosis of atrial fibrillation (AF) is essential to reduce complications from this increasingly common condition. We sought to assess the diagnostic accuracy of smartphone camera photoplethysmography (PPG) compared with conventional electrocardiogram (ECG) for AF detection.MethodsThis is a systematic review of MEDLINE, EMBASE and Cochrane (1980–December 2020), including any study or abstract, where smartphone PPG was compared with a reference ECG (1, 3 or 12-lead). Random effects meta-analys… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
31
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 27 publications
(31 citation statements)
references
References 35 publications
0
31
0
Order By: Relevance
“…Standard 12-lead ECG equipment could not be made available in such circumstances, but the widespread use of smartphones might provide the groundwork for a wider use of electrocardiography. [18][19][20] Our research revealed a high degree of STEMI accuracy across Spandan smartphone ECG records and traditional ECG readings. The 12 lead Spandan smartphone ECG has superior diagnostic capabilities for STEMI when compared to simultaneously conducted traditional 12L ECG in a primary care population, according to blinded cardiologists.…”
Section: Resultsmentioning
confidence: 69%
“…Standard 12-lead ECG equipment could not be made available in such circumstances, but the widespread use of smartphones might provide the groundwork for a wider use of electrocardiography. [18][19][20] Our research revealed a high degree of STEMI accuracy across Spandan smartphone ECG records and traditional ECG readings. The 12 lead Spandan smartphone ECG has superior diagnostic capabilities for STEMI when compared to simultaneously conducted traditional 12L ECG in a primary care population, according to blinded cardiologists.…”
Section: Resultsmentioning
confidence: 69%
“…14 It would be unfeasible to provide standard 12-lead ECG devices in such settings, but smartphone penetration has already become commonplace and has potential to provide foundation for greater spread of ECG. [15][16][17] Our study showed a good degree of accuracy for STEMI between Spandan smartphone ECG and standard ECG recordings. The diagnostic properties of the 12 lead Spandan smartphone ECG as assessed by blinded cardiologists against simultaneously performed standard 12L ECG in a primary care population were excellent for STEMI.…”
Section: Discussionmentioning
confidence: 58%
“…However, the validation of these devices remains unclear, and the AF they describe may not be associated with the same degree of impact on stroke and thromboembolism. [ 44 , 45 ] Incident cardiac and cerebral event rates may also be dependent on the ‘severity’ of HFpEF and the degree of underlying systolic impairment in AF, even if above an LVEF of 50%. [ 46 ] The value of additional physiological assessment remains unclear (e.g.…”
Section: Diagnostic Challenges For Heart Failure With Preserved Eject...mentioning
confidence: 99%